Preliminary Study on Water Quality and Heteropterans Diversity in a Semi-Urban Stream (Central Region of Cameroon) - Jean Dzavi; Samuel Foto Menbohan; Blaise Rollinat Mboye; Leonelle Tsowa Pianta; Audrey Glwadys Nzépang Tchizé; Amandine Laure Toumbou Nouazi; Eric Belmond Biram à Ngon; Gloria Eneke Takem (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
A study was conducted in the Konglo stream for six months to make an inventory of aquatic heteroptera, following a monthly sampling frequency. Some hydrological and physicochemical parameters such as water width, current velocity, and water flow, water temperature and pH, electrical conductivity, dissolved oxygen, total hardness, phosphates, nitrates, and ammonia were measured according to standard methods. For an inventory of the heteropterans, the multihabitat approach was used during sampling, but only heteropterans representing 3.15 % of total abundance are considered in this study. The hydrological variables were different in each station. The water width and flow were increased from upstream to downstream. The results showed that pH, total hardness, nitrites, phosphates, and ammonia values ​​were weak and no significant differences were observed. Among physicochemical variables, only dissolved oxygen and electrical conductivity were different between upstream and downstream. The conductivity increased from upstream to downstream while the dissolved oxygen was very low downstream. 62 individuals were collected and counted belonging to 11 taxa, the most abundant being Ranatra linearis. The other taxa such as Anisops sp., Aphelocheirus aestivalis, Gerris sp., Gerridae Nd., Hydrometra sp., Ilyocoris cimicoides, Naucoris sp., Nepa sp., Notonectidae Nd., and Velia sp. were poorly represented. High abundance was recorded at the upstream (38 individuals), but the taxonomic richness (3 taxa) and diversity (0.24 bits/ind) remain low, unlike the stations located downstream (7 taxa and 1.82 bits/ind).